Avalanche mediated devitrification in a glass of pseudo hard-spheres. (29th September 2016) - Rosales-Pelaez, P; de Hijes, P Montero; Sanz, E; Valeriani, C
Abstract: By means of molecular dynamics we analyse several aspects of the avalanche-mediated mechanism for glass crystallization recently reported for hard sphere glasses (Sanz et al 2014 Proc. Natl Acad. Sci . 111 75). To investigate the role of inter-particle interaction softness on the devitrification path we use a continuous version of the hard-sphere potential: the pseudo-hard sphere potential (Jover et al 2012 J. Chem. Phys . 137 144505). We observe the same crystallization mechanism as in hard spheres. However, pseudo-hard sphere glasses crystallise earlier for a given density because the development of avalanches is eased by the small degree of overlapping allowed. We analyse the impact of density on the devitrification mechanism. When increasing the density, the avalanche mechanism becomes more evident and crystallisation is retarded due to a decrease of the avalanche emergence likelihood. To conclude, the observed avalanche-mediated mechanism and its density dependence do not substantially change with the employed simulation ensemble (constant volume versus constant pressure).